Photosensitizer for degrading cefotaxime sodium as well as preparation method and application of photosensitizer

By combining phosphorus-doped graphite phase carbon nitride with 3,4,9,10-perylene tetraformyl diimine, an all-organic heterojunction photosensitive agent is formed, which solves the low solar conversion efficiency of graphite phase carbon nitride photosensitizer. The problem of this method achieves the effect of efficient degradation of ceftaxime sodium and maintains stability under different pH conditions.

CN119158620APending Publication Date: 2024-12-20HUNAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411297396.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing graphite phase carbon nitride (g-C3N5) photosensitizers are not ideal in solar energy conversion efficiency, and their modification methods are complex and costly, making it difficult to effectively degrade organic pollutants.

Method used

By in situ recrystallization on the surface of phosphorus-doped graphite phase carbon nitride, composited with 3,4,9,10-perylene tetraformyl diimine, forming a phosphorus-doped graphite phase carbon nitride-based all-organic heterojunction photosensitizer. Improve its photocatalytic activity and degradation efficiency.

Benefits of technology

This photosensitizer significantly improves the degradation efficiency of cefotaxime sodium under visible light, has good light absorption capacity and stability, and can effectively remove cefotaxime sodium antibiotics in aqueous environments under weak acid and alkaline conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158620A_ABST
    Figure CN119158620A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photocatalytic water treatment, in particular to a photosensitizer for degrading cefotaxime sodium as well as a preparation method and application of the photosensitizer. Carrying out in-situ recrystallization on the surface of phosphorus-doped graphite phase carbon nitride on 3, 4, 9, 10-perylenetetracarboxylic diimide to obtain a photosensitizer; the phosphorus-doped graphite phase carbon nitride is of a granular blocky structure, and the 3, 4, 9, 10-perylenetetracarboxylic diimide is of a rodlike structure. The photosensitizer provided by the invention has the advantages of good light absorption capacity, good photocatalytic performance, good stability and the like, is a novel carbon nitride-based photosensitizer material, and experiments verify that the photosensitizer material can effectively remove cefotaxime sodium antibiotics in a water environment under weak acid and alkaline conditions, so that the photosensitizer material has good application prospects. A new thought is provided for degrading the cefotaxime sodium antibiotics in the water environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalytic water treatment, and in particular to a photosensitizer for degrading ceftriaxone sodium, and a preparation method and application thereof. Background Art

[0002] Graphitic carbon nitride (gC 3 N 5 ) is a metal-free nanophotosensitizer. 3 N 5 The skeleton characteristics describe and reveal its unique electronic structure and optical properties. Its unique skeleton characteristics make it have a small band gap, high charge-hole separation efficiency, and a wide visible light absorption range. The higher nitrogen atomic content can also promote C 3 N 5 In addition, compared with some traditional iron-based and bismuth-based photocatalysts, C 3 N 5 With an adjustable electronic structure, it is a very environmentally friendly and stable structure, C 3 N 5 Easy to maintain and non-polluting photosensitizer. However, gC 3 N 5 It can only absorb sunlight with a wavelength less than 500nm, and its solar energy conversion efficiency is still not ideal.

[0003] In order to further improve gC 3 N 5 In order to improve the photocatalytic conversion efficiency, various modification methods including structural regulation, doping with heteroelements, semiconductor or carbon material composites, etc. have been widely reported to increase the reaction active sites, enhance light absorption and improve the separation / migration ability of carriers.

[0004] However, the synthesis of the above methods is still a challenge. Therefore, it is urgent to develop a stable, low-cost and effective modification method to improve gC 3 N 5 Photocatalytic activity to degrade organic pollutants. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a photosensitizer for degrading ceftriaxone sodium, and a preparation method and application thereof. The photosensitizer provided by the present invention can efficiently degrade ceftriaxone sodium.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides a photosensitizer for degrading ceftriaxone sodium. The phosphorus-doped graphite phase carbon nitride surface is in-situ recrystallized on 3,4,9,10-perylenetetracarboxylic acid diimide to obtain the photosensitizer.

[0008] The phosphorus-doped graphite-phase carbon nitride is a particle block structure, and the 3,4,9,10-perylenetetracarboxylic acid diimide is a rod structure.

[0009] The present invention also provides a method for preparing the photosensitizer described in the above technical solution, comprising the following steps:

[0010] 1) mixing 3-amino-1,2,4-triazole and tripolyphosphazene chloride, and then sequentially performing thermal polymerization reaction and copolymerization heat treatment to obtain phosphorus-doped graphite phase carbon nitride;

[0011] 2) Ultrasonic mixing of the phosphorus-doped graphite phase carbon nitride obtained in step 1) with a 3,4,9,10-perylenetetracarboxylic acid diimide solution and water, and allowing the mixture to stand to obtain a photosensitizer.

[0012] Preferably, in step 1), the mass ratio of 3-amino-1,2,4-triazole to tripolyphosphazene chloride is 2:0.12.

[0013] Preferably, the conditions of the thermal polymerization reaction in step 1) include: temperature of 500° C., time of 4 hours, and heating rate of 5° C. / min.

[0014] Preferably, the conditions of the copolymerization heat treatment in step 1) include: temperature of 550° C., time of 4 h, and heating rate of 5° C. / min.

[0015] Preferably, in step 2), the volume ratio of the mass of phosphorus-doped graphite-phase carbon nitride to the volume of 3,4,9,10-perylenetetracarboxylic acid diimide solution and water is 0.6 g:10 mL:100 mL;

[0016] The solvent of the 3,4,9,10-perylenetetracarboxylic acid diimide solution is concentrated sulfuric acid, and the mass ratio of the volume of the concentrated sulfuric acid to the 3,4,9,10-perylenetetracarboxylic acid diimide is 10 mL:0.1 g.

[0017] Preferably, the ultrasonic mixing time in step 2) is 10 min and the power is 150 W;

[0018] The standing time is 0.5h.

[0019] The present invention also provides the use of the photosensitizer described in the above technical solution in degrading ceftriaxone sodium in water.

[0020] Preferably, the photosensitizer is mixed with water to carry out a photocatalytic reaction under visible light.

[0021] Preferably, the dosage of the photosensitizer is 0.2 g / L, and the concentration of ceftriaxone sodium in the water is 20 mg / L;

[0022] The mixing conditions include: first ultrasonication for 10 minutes and then dark reaction for 20 minutes;

[0023] The photocatalytic reaction time is more than 135 minutes.

[0024] The mechanism of the present invention for improving the degradation effect of ceftriaxone sodium is:

[0025] Because gC 3 N 5 There is an aromatic heterocyclic structure, and the rigid planar structure of PDI has a delocalized large π bond, gC 3 N 5 and PDI can be tightly bound through π–π interactions and NC bonds. 3 N 5 , lowering the band structure to make it more compatible with PDI. The electron delocalization effect, built-in electric field and newly formed interfacial chemical bonds jointly promote the interaction between PDI and PgC 3 N 5 The separation and migration of photogenerated carriers between 3 N 5 During the photocatalytic degradation of ceftriaxone sodium by PDI, ceftriaxone sodium will also be adsorbed on the catalyst surface due to π-π interaction, and various active species ( 1 O 2 、h + , ·O 2 - and H 2 O 2 )), the main one is 1 O 2 It will preferentially react with the unsaturated double bonds in the adsorbed cefotaxime sodium molecules to form a ring-opening reaction, and then undergo subsequent degradation and mineralization.

[0026] Beneficial effects:

[0027] The photosensitizer provided by the present invention has the advantages of good light absorption ability, good photocatalytic performance, good stability, etc., and is a new type of carbon nitride-based photosensitizer material. Experiments have verified that the photosensitizer material can effectively remove the ceftriaxone sodium antibiotic in the water environment under weak acid and alkaline conditions, providing a new idea for degrading the ceftriaxone sodium antibiotic in the water environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the embodiments are briefly introduced below.

[0029] Figure 1 The phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic heterojunction photosensitizer (6-PC 3 N5 / PDI) SEM images;

[0030] Figure 2 The phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic heterojunction photosensitizer (6-PC 3 N 5 / PDI) TEM image;

[0031] Figure 3 XRD patterns of different photosensitizers;

[0032] Figure 4 XPS spectra of different photosensitizers;

[0033] Figure 5 Fourier transform infrared spectra of different photosensitizers;

[0034] Figure 6 UV-visible diffuse reflectance spectra of different photosensitizers;

[0035] Figure 7 This is a graph showing the degradation effect of the phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic heterojunction photosensitizer prepared in Example 1 of the present invention on cefotaxime sodium;

[0036] Figure 8 This is the degradation effect of different photosensitizers on ceftriaxone sodium;

[0037] Fig. 9 This is a graph showing the degradation effect of the phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic heterojunction photosensitizer prepared in Example 1 of the present invention on ceftriaxone sodium solutions with different pH values;

[0038] Fig.10 This is a graph showing the degradation effect of ceftriaxone sodium being repeatedly treated with the phosphorus-doped graphite-phase carbon nitride-based and perylene diimide all-organic heterojunction photosensitizer prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0039] The present invention provides a photosensitizer for degrading ceftriaxone sodium, wherein the phosphorus-doped graphite phase carbon nitride surface is in-situ recrystallized on 3,4,9,10-perylenetetracarboxylic acid diimide to obtain the photosensitizer; the phosphorus-doped graphite phase carbon nitride is a particle block structure, and the 3,4,9,10-perylenetetracarboxylic acid diimide is a rod-shaped structure. In the present invention, in the photosensitizer, P is dispersed in gC at a single atomic level. 3 N 5 In the skeleton, a PN / P=N bond is formed.

[0040] The present invention provides a method for preparing the photosensitizer described in the above technical solution, comprising the following steps:

[0041] 1) mixing 3-amino-1,2,4-triazole and tripolyphosphazene chloride, and then sequentially performing thermal polymerization reaction and copolymerization heat treatment to obtain phosphorus-doped graphite phase carbon nitride;

[0042] 2) Ultrasonic mixing of the phosphorus-doped graphite phase carbon nitride obtained in step 1) with a 3,4,9,10-perylenetetracarboxylic acid diimide solution and water, and allowing the mixture to stand to obtain a photosensitizer.

[0043] The invention mixes 3-amino-1,2,4-triazole and tripolyphosphazene chloride, and then sequentially performs thermal polymerization reaction and copolymerization heat treatment to obtain phosphorus-doped graphite phase carbon nitride.

[0044] In the present invention, the mass ratio of the 3-amino-1,2,4-triazole to tripolyphosphazene chloride is preferably 2:0.12. In the present invention, the 3-amino-1,2,4-triazole and tripolyphosphazene chloride are preferably mixed and ground, vacuum dried, and then subjected to thermal polymerization reaction and copolymerization heat treatment. The present invention does not specifically limit the conditions of the grinding and vacuum drying, and those skilled in the art can use conventional methods. In the present invention, the conditions of the thermal polymerization reaction preferably include: a temperature of 500°C, a time of 4h, and a heating rate of 5°C / min. In the present invention, the conditions of the copolymerization heat treatment preferably include: a temperature of 550°C, a time of 4h, and a heating rate of 5°C / min.

[0045] The method comprises ultrasonically mixing the obtained phosphorus-doped graphite phase carbon nitride with a 3,4,9,10-perylenetetracarboxylic acid diimide solution and water, and allowing the mixture to stand to obtain a photosensitizer.

[0046] In the present invention, the mass ratio of the phosphorus-doped graphite phase carbon nitride to the volume of the 3,4,9,10-perylenetetracarboxylic acid diimide solution and the volume ratio of water is preferably 0.6g:10mL:100mL. In the present invention, the solvent of the 3,4,9,10-perylenetetracarboxylic acid diimide solution is preferably concentrated sulfuric acid, and the volume ratio of the concentrated sulfuric acid to the mass ratio of 3,4,9,10-perylenetetracarboxylic acid diimide is 10mL:0.1g. The present invention preferably adopts ultrasound for 10 minutes to completely dissolve the 3,4,9,10-perylenetetracarboxylic acid diimide in concentrated sulfuric acid. The present invention does not specifically limit the conditions of the ultrasound, and those skilled in the art can use conventional methods.

[0047] In the present invention, the ultrasonic mixing time is preferably 10 minutes, the power is preferably 150W; the standing time is preferably 0.5 hours. After standing, the present invention preferably filters the standing object through a 0.45 μm membrane filter, collects the filtered solid, washes with deionized water, and dries to obtain a photosensitizer. In the present invention, the drying conditions preferably include: a temperature of 80°C and a time of 4 hours.

[0048] The present invention also provides the use of the photosensitizer described in the above technical solution in the degradation of ceftriaxone sodium in water. The present invention preferably mixes the photosensitizer with water and performs a photocatalytic reaction under visible light. In the present invention, the dosage of the photosensitizer is preferably 0.2 g / L, and the concentration of ceftriaxone sodium in the water is preferably 20 mg / L. In the present invention, the mixing conditions preferably include: first ultrasonication for 10 minutes and then dark reaction for 20 minutes. In the present invention, the time of the photocatalytic reaction is preferably more than 135 minutes.

[0049] In order to further illustrate the present invention, the present invention is described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0050] Example 1

[0051] (1) Phosphorus-doped C 3 N 5 The nanosheets are called PC 3 N 5 , take 5 alumina crucibles respectively, use an analytical balance to weigh 2g of 3-AT (3-amino-1,2,4-triazole, content 96%) and 0.12g of HCCP (tripolychlorophosphazene, content 98%) in a mortar, mix thoroughly and then grind. After grinding, the obtained precursor is vacuum dried, and after drying, it is placed in a crucible respectively, and the crucible is placed in a muffle furnace. The heating program is set: thermal polymerization at 500°C for 4h (heating rate is 5°C / min). After the product is naturally cooled, it is ground again and placed in a muffle furnace for copolymerization heat treatment. The heating time is set to 4h, the heating rate is 5°C / min, and the target temperature is 550°C. After the product is naturally cooled, PC is obtained. 3 N 5 sample.

[0052] (2) Weigh 0.1 g of PDI (3,4,9,10-perylenetetracarboxylic acid diimide) and dissolve it in a beaker containing 10 mL of concentrated sulfuric acid under ultrasonic treatment. Ultrasonicate the beaker for 10 min to fully dissolve it. Weigh 0.6 g of PC 3 N 5 Add to the beaker, add 100mL of deionized water to the beaker, and continue ultrasonication for 10 minutes. At this time, a solid insoluble precipitate will immediately appear in the beaker, and stand for 0.5 hours. Then filter through a 0.45μm membrane filter, collect the filtered solid, and wash it with deionized water several times. After washing, collect it and put it in a beaker, put the beaker into a drying oven for drying, the drying temperature is 80℃, and the drying time is 4 hours. After drying, PC is obtained 3 N 5 / PDI and marked as 6-PC 3 N5 PDI.

[0053] Figure 1 The phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic heterojunction photosensitizer (6-PC 3 N 5 / PDI) SEM picture. Figure 1 It can be seen that PDI is rod-shaped and PC 3 N 5 It is granular and blocky, and you can see PC 3 N 5 The surface of the prepared composite photosensitizer material is uneven and irregular, and the surface of the photosensitizer material is rough and has many gaps. Such structural characteristics can increase the specific surface area of ​​the photosensitizer material and increase the contact area with cephalosporin antibiotics per unit time, thereby accelerating the speed of the photosensitizer material to produce singlet oxygen, thereby improving the degradation efficiency.

[0054] Figure 2 The phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic heterojunction photosensitizer (6-PC 3 N 5 / PDI) TEM image. Figure 2 It can be seen that it has a good lattice structure, indicating that PC 3 N 5 Successfully reunited with PDI and maintained close ties.

[0055] Figure 3 The phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic heterojunction photosensitizer (6-PC 3 N 5 / PDI), PC 3 N 5 、XRD pattern of PDI. Figure 3 It can be seen that for PDI and 6-PC 3 N 5 For PC / PDI, the peak at 27.5° corresponds to the interlayer stacking of aromatic units. 3 N 5 and 6-PC 3 N 5 As for PDI, two diffraction peaks were observed at 11.7° and 27.1°, respectively, on the (001) plane and on the C composed of triazole. 3 N 5 The interlayer stacking of the units shows that the experiment successfully composited the two materials.

[0056] Figure 4The phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic heterojunction photosensitizer (6-PC 3 N 5 / PDI), PC 3 N 5 、PDI XPS chart. Figure 4 It can be seen that the three photosensitizer materials all have four elements: C, N, O, and P. In the C1s spectrum, the peaks near the binding energies of 288.4eV, 286.3eV, and 284.8eV are assigned to NC=N, COC, and CC peaks, respectively. In the N1s spectrum, the peaks near the binding energies of 400.5eV and 398.8eV are assigned to CN=C, N-(C) 3 In the O1s spectrum, the peaks near the binding energies of 533.2eV and 531.6eV are assigned to the C=O and CO peaks, respectively. In the P 2p spectrum, the peaks near the binding energies of 134.5eV and 133.1eV are assigned to the PN and P=N peaks, respectively. The analysis and comparison of the XPS total spectrum and the high-resolution spectra of the four elements C, N, O, and P of the three photosensitizers further demonstrate that the composite photosensitizer material was successfully synthesized.

[0057] Figure 5 The phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic heterojunction photosensitizer (6-PC 3 N 5 / PDI), PC 3 N 5 、Fourier infrared spectrum of PDI. Figure 5 It can be seen from the figure that 6-PC 3 N 5 / PDI at 1251cm -1 , 1324cm -1 The peak is due to the stretching vibration of CN and PN heterocyclic rings and is located at 808 cm -1 The peak of 1688 cm corresponds to the vibration peak of triazine unit. -1 The peak at 1579 cm is attributed to the stretching vibration of the carboxyl group in the molecule. -1 The stretching vibration peak at 1324 cm is caused by the ketone functional group in the molecule. -1 and 1408cm -1 The absorption peak at 1579 cm is attributed to the stretching vibration of -COO-. -1 The absorption band at is attributed to the C=C group in the aromatic carbon skeleton. By comparing PDI and PC 3 N 5 Infrared spectrum of 6-PC 3 N 5In the PDI / PDI heterojunction structure, PDI and PC can be found 3 N 5 All the peaks indicate that they contain the chemical bonds contained in both. These results indicate that the composite photosensitizer material was successfully synthesized and the chemical structure and crystal structure were not affected.

[0058] Figure 6 The phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic heterojunction photosensitizer (6-PC 3 N 5 / PDI), PC 3 N 5 、UV-visible diffuse reflectance graph of PDI. Figure 6 It can be seen that PC 3 N 5 It can only absorb light with a wavelength below 400nm, and its light response ability is poor. PDI has a certain light absorption ability within the range of 600nm, but the light absorption ability is weak, while 6-PC 3 N 5 / PDI shows strong absorption in the range of 600nm, and the wavelength range of absorbed light is wider than that of PC 3 N 5 And PDI is larger, indicating that the light absorption capacity of the material has been enhanced after compounding, and the light response ability is better.

[0059] Combination Figure 1-6 It can be seen that the phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic heterojunction photosensitizer (6-PC 3 N 5 / PDI) has the advantages of strong light absorption ability, low photogenerated electron-hole recombination rate and good photocatalytic performance.

[0060] Comparative Example 1

[0061] 0.6 g of PC from step (2) of Example 1 3 N 5 Changed to 0.2g PC 3 N 5 , other conditions remain unchanged, and are marked as 2-PC 3 N 5 PDI.

[0062] Comparative Example 2

[0063] 0.6 g of PC from step (2) of Example 1 3 N 5 Changed to 0.4g PC 3 N 5 , other conditions remain unchanged, and are marked as 4-PC 3 N5 PDI.

[0064] Comparative Example 3

[0065] 0.6 g of PC from step (2) of Example 1 3 N 5 Changed to 0.8g PC 3 N 5 , other conditions remain unchanged, and marked as 8-PC 3 N 5 PDI.

[0066] Comparative Example 4

[0067] 0.6 g of PC from step (2) of Example 1 3 N 5 Changed to 1.0g PC 3 N 5 , other conditions remain unchanged, and are marked as 10-PC 3 N 5 PDI.

[0068] Example 2

[0069] The application of the phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic heterojunction photosensitizer prepared in Example 1 and Comparative Examples 1-4 in removing organic pollutants in water bodies, specifically using the phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic heterojunction photosensitizer to photocatalytically remove ceftriaxone sodium in water bodies, comprises the following steps:

[0070] The phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic heterojunction photosensitizer (6-PC 3 N 5 / PDI), the photosensitizer prepared in Comparative Example 1 (2-PC 3 N 5 / PDI), the photosensitizer prepared in Comparative Example 2 (4-PC 3 N 5 / PDI), the photosensitizer prepared in Comparative Example 3 (8-PC 3 N 5 / PDI), the photosensitizer prepared in Comparative Example 4 (10-PC 3 N 5 / PDI), take 0.02g each, add them to 100mL of 20mg / L cefotaxime sodium antibiotic solution, mix them evenly, pour the solution into the photoreaction bottle, sample with a 2.5mL sterile syringe, and then use a 0.22μm water-based needle filter to inject into the sample tube, record it as the original sample. After ultrasonication for 10min (power 150W), dark reaction for 20min, then sample, mark it as dark reaction sampling. After sampling, put the magnet into the photoreaction bottle, turn the switch, and the magnet will automatically rotate and stir. After connecting the circulating water, turn on the fan of the Xe lamp (power 300W) reactor, use a filter to filter out ultraviolet light, use visible light for photocatalytic reaction, use a 0.22μm water-based needle filter to sample every 15min, and sample 2mL each time, for a total of nine times. The sample is sealed and stored in a 2.5mL sample tube.

[0071] Control group 1: PC 3 N 5 Replacement 6-PC 3 N 5 / PDI, other conditions being the same.

[0072] Control group 2: PDI replaced 6-PC 3 N 5 / PDI, other conditions being the same.

[0073] At the same time, in this embodiment, phosphorus-doped graphite phase carbon nitride-perylene diimide all-organic heterojunction photosensitizer (6-PC 3 N 5 / PDI) on the degradation effect of ceftriaxone sodium antibiotic solution with different pH values ​​(other conditions are the same as those in Example 3) and phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic heterojunction photosensitizer (6-PC 3 N 5 / PDI) to the stability of the degradation of ceftriaxone sodium antibiotic solution. Figure 7 , Figure 8 , Fig. 9 , Fig.10 shown.

[0074] Figure 7 The figure is a graph showing the degradation effects of five phosphorus-doped graphite-phase carbon nitride-based and perylene diimide all-organic heterojunction photosensitizers prepared in Example 1 of the present invention on cefotaxime sodium. Figure 7 It can be seen from the figure that C / C 0 It can be seen that after half an hour of dark reaction, the five photosensitizer materials prepared in the experiment all degraded ceftriaxone sodium to a certain extent. After the start of light irradiation, the degradation rate of ceftriaxone sodium by the five photosensitizer materials showed an accelerated trend, but after 1 hour of light irradiation, it can be found that 2-PC 3 N 5 / PDI, 4-PC 3 N 5 / PDI, 10-PC 3 N 5 / PDI degradation rate began to slow down, while 6-PC 3 N 5 / PDI and 8-PC 3 N 5 / PDI still showed an accelerated state. After 135 minutes of light exposure, 6-PC 3 N 5 The degradation degree of / PDI on ceftriaxone sodium is as high as 84%, which is the best degradation effect among the five composite photosensitizer materials prepared in the experiment.

[0075] Figure 8 The figure shows the degradation effect of different photosensitizers on ceftriaxone sodium. Figure 8 (a) It can be seen from the figure that C / C 0 It can be clearly seen that after half an hour of dark reaction, the three photosensitizer materials all degraded ceftriaxone sodium to a certain extent, and the best degradation effect was achieved by 6-PC 3 N 5 After the illumination, the degradation rate of ceftriaxone sodium by the three photosensitizer materials showed an accelerating trend, but the degradation efficiency of PDI for ceftriaxone sodium was about 10%, which was not ideal. 3 N 5 and 6-PC 3 N 5 The degradation effect of PC / PDI on ceftriaxone sodium increased with time. After 135 min of illumination, 3 N 5 The degradation degree of ceftriaxone sodium reached 70%, and 6-PC 3 N 5 The degradation degree of cefotaxime sodium by PDI was as high as 84%, which indicated that the 6-PC 3 N 5 / PDI has better degradation effect than two single photosensitizers and can degrade ceftriaxone sodium antibiotics well. Figure 8 (b) It can be seen that the degradation of ceftriaxone sodium by the three photosensitizer materials is a straight line, which is a first-order reaction in terms of kinetics. Figure 8 (c) It can be seen that the degradation rate constants of the three materials are obtained by calculating the slope k. It can be seen that 6-PC 3 N 5 The degradation rate constant of / PDI is 9.341×10 -3 min -1 , larger than PC 3 N 5And PDI. This shows that the composite photosensitizer material has a more efficient degradation efficiency.

[0076] Fig. 9 This is a graph showing the degradation effect of the phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic heterojunction photosensitizer prepared in Example 1 of the present invention on ceftriaxone sodium solutions with different pH values. Fig. 9 The photosensitizer material (6-PC 3 N 5 The degradation efficiency of 6-PC / PDI on cefotaxime sodium. 3 N 5 / PDI still has a degradation effect on ceftriaxone sodium in water environment, and the degradation effect at pH=6 is the most ideal.

[0077] Fig.10 This is a graph showing the degradation effect of repeated treatment of cefotaxime sodium by the phosphorus-doped graphite phase carbon nitride-perylene diimide all-organic heterojunction photosensitizer prepared in Example 1 of the present invention. Fig.10 It can be seen that including the dark reaction for 30 min, within the reaction time of 135 min, 6-PC 3 N 5 The degradation rate of the / PDI photosensitizer material for the antibiotic ceftriaxone sodium has remained above 80%. The experiment showed that after three consecutive cycles of experiments, the photosensitizer material can still maintain a relatively high degradation activity. This shows that the photocatalytic degradation stability of the photosensitive material is good, which provides a certain guarantee for its practical application in the future. The photosensitizer material successfully prepared in the experiment provides a new way to photocatalytically degrade ceftriaxone sodium in water environment.

[0078] In summary, the phosphorus-doped graphite phase carbon nitride-based and perylene diimide all-organic heterojunction photosensitizer of the present invention has the advantages of good light absorption ability, good photocatalytic performance, good stability, etc., and is a new type of carbon nitride-based photosensitizer material. Experiments have verified that the photosensitizer material can effectively remove ceftriaxone sodium antibiotics in water environments under weak acid and alkaline conditions, providing a new idea for degrading ceftriaxone sodium antibiotics in water environments.

[0079] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A photosensitizer for degrading ceftriaxone sodium, characterized in that: Phosphorus-doped graphite-phase carbon nitride was in situ recrystallized on 3,4,9,10-perylenetetracarboxylic acid diimide to obtain a photosensitizer; The phosphorus-doped graphite-phase carbon nitride is a particle block structure, and the 3,4,9,10-perylenetetracarboxylic acid diimide is a rod structure.

2. A method for preparing the photosensitizer according to claim 1, characterized in that: The following steps are involved: 1) mixing 3-amino-1,2,4-triazole and tripolyphosphazene chloride, and then sequentially performing thermal polymerization reaction and copolymerization heat treatment to obtain phosphorus-doped graphite phase carbon nitride; 2) Ultrasonic mixing of the phosphorus-doped graphite phase carbon nitride obtained in step 1) with a 3,4,9,10-perylenetetracarboxylic acid diimide solution and water, and allowing the mixture to stand to obtain a photosensitizer.

3. The preparation method according to claim 1, characterized in that: In the step 1), the mass ratio of 3-amino-1,2,4-triazole to tripolyphosphazene chloride is 2:0.

12.

4. The preparation method according to claim 1, characterized in that: The conditions of the thermal polymerization reaction in step 1) include: temperature of 500° C., time of 4 hours, and heating rate of 5° C. / min.

5. The preparation method according to claim 1, characterized in that: The conditions of the copolymerization heat treatment in step 1) include: temperature of 550° C., time of 4 hours, and heating rate of 5° C. / min.

6. The preparation method according to claim 1, characterized in that: In the step 2), the volume ratio of the phosphorus-doped graphite-phase carbon nitride to the volume of the 3,4,9,10-perylenetetracarboxylic acid diimide solution and water is 0.6 g: 10 mL: 100 mL; The solvent of the 3,4,9,10-perylenetetracarboxylic acid diimide solution is concentrated sulfuric acid, and the mass ratio of the volume of the concentrated sulfuric acid to the 3,4,9,10-perylenetetracarboxylic acid diimide is 10 mL:0.1 g.

7. The preparation method according to claim 1, characterized in that: The ultrasonic mixing time of step 2) is 10 min and the power is 150 W; The standing time is 0.5h.

8. Use of the photosensitizer according to claim 1 in degrading ceftriaxone sodium in water.

9. The use according to claim 8, characterized in that: The photosensitizer is mixed with water to carry out a photocatalytic reaction under visible light.

10. The use according to claim 9, characterized in that: The dosage of the photosensitizer is 0.2 g / L, and the concentration of ceftriaxone sodium in the water is 20 mg / L; The mixing conditions include: first ultrasonication for 10 minutes and then dark reaction for 20 minutes; The photocatalytic reaction time is more than 135 minutes.